An unexpected challenge: intra-abdominal neurofibromatosis during biliary reconstruction: a case report - Alireza Firouzfar; Pouria Abedini; Parsa Elyasi Bakhtiari; Behnam Sanei (Annals of Medicine & Surgery, 2026)
Introduction and importance: Neurofibromatosis type 1 (NF1) is a genetic disorder characterized by peripheral nerve sheath tumors in the skin or nervous system. Its prevalence is 1 in 2600–3000 individuals, but intra-abdominal manifestations appear in only 5–25% of these patients, which makes this presentation a rare medical condition. The presence of intra-abdominal lesions can significantly complicate surgical procedures and render biliary reconstruction technically challenging. Case presentation: This case describes an uncommon presentation of visceral NF1 in a 75-year-old woman with cutaneous NF1 lesions, who was admitted to our hospital with right upper quadrant pain and jaundice. Preoperative imaging studies showed a dilated and tortuous common bile duct, filled with multiple stones. Because of prior unsuccessful endoscopic retrograde cholangiopancreatography procedures, an elective choledochotomy was performed. During surgery, widespread intra-abdominal neurofibromas were noted throughout the small intestine, posing significant difficulty in finding a suitable, tumor-free site for biliary-enteric anastomosis. Clinical discussion: Visceral involvement in NF1 is rare but can present major diagnostic and surgical challenges. Gastrointestinal neurofibromas may remain asymptomatic until they cause obstruction, bleeding, or jaundice. Surgical management demands special consideration when neurofibromas diffusely infiltrate the mesentery or bowel wall, as they complicate both exposure and reconstruction. The main challenge of this case was finding an area without neurofibroma lesions in the small intestine for anastomosis to prevent postoperative complications. Conclusion: This case highlights the importance of managing patients with gastrointestinal manifestations of NF1 who require abdominal surgical intervention.